Synthesis, characterization, and gas permeability of aromatic polyimides containing pendant phenoxy group - Kothawade, Sandeep S.; Kulkarni, Mahesh P.; Kharul, Ulhas K.; Patil, Anandrao S.; Vernekar, Subhash P. (Journal of Applied Polymer Science, 2008)
A diamine containing a pendant phenoxy group, 1-phenoxy-2,4-diaminobenzene, was synthesized and condensed with different aromatic dianhydrides [4,4'-oxydiphthalic dianhydride, 4,4'-(hexafluoroisopropylidene)diphthalic anhydride, 3,3',4,4-benzophenone tetracarboxylic dianhydride, 3,3',4,4'-biphenyltetracorboxylic dianhydride, and pyromellitic dianhydride] by one-step synthesis at a high temperature in m-cresol to obtain polyimides in high yields. Most of the polyimides exhibited good solvent solubility and could be readily dissolved in chloroform, sym-tetrachloroethane, N,N-dimethylformamide, NN-dimethylacetamide, and nitrobenzene. Their inherent viscosities were in the range of 0.33-1.16 dL/g. Wide-angle X-ray spectra revealed that these polymers were amorphous in nature. All these polyimides were thermally stable, having initial decomposition temperatures above 500 degrees C and glass-transition temperatures in the range of 248-281 degrees C. The gas permeability of 4,4'-oxydiphthalic dianhydride and 4,4'-(hexafluoroisopropylidene)diphthalic anhydride based polyimides was investigated with pure gases: He, H-2, O-2, Ar, N-2, CH4, and CO2. A polyimide containing a -C(CF3)(2)- linkage showed a good combination of permeability and selectivity. (C) 2008 Wiley Periodicals, Inc.
Keywords: Gas permeation; membranes; polyimides; selectivity; structure-property relations

Poly(amideimide)s containing pendant pentadecyl chains: synthesis and characterization - More, Arvind S.; Patil, Anandrao S.; Wadgaonkar, Prakash P. (Polymer Degradation and Stability, 2010)
A new aromatic diacylhydrazide monomer viz., 4-[4'-(hydrazinocarbonyl)phenoxy]-2- pentadecylbenzo-hydrazide was synthesized starting from cardanol, which in turn is obtainable from cashew nut shell liquid a renewable resource material. A series of new poly(amideimide)s containing flexibilizing ether linkages and pendant pentadecyl chains was synthesized from 4-[4'-(hydrazinocarbonyl)phenoxy]-2-pentade-cylbenzohydrazide and commercially available aromatic dianhydrides, viz., benzene-1,2,4,5-tetracarboxylic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, benzophenone-3,3',4,4'-tetracarboxylic dianhydride, 4,4'-oxydiphthalic anhydride and 4,4'-(hexafluoro isopropylidene)diphthalic anhydride by a two-step solution polycondensation in N,N-dimethylacetamide via the poly(hydrazide acid) intermediate. Inherent viscosities of poly(amideimide)s were in the range 0.60-0.64 dL/g in N,N-dimethylacetamide at 30 +/- 0.1 degrees C. Poly(amideimide)s could be solution cast into tough, transparent and flexible films from their N,N-dimethylacetamide solutions. The solubility of poly(amideimide)s was significantly improved by incorporation of pendant pentadecyl chains and were found to be soluble in N,N-dimethylacetamide, 1-methyl-2-pyrrolidinone, pyridine and m-cresol at room temperature or upon heating. Wide angle X-ray diffraction patterns of poly(amideimide)s revealed a broad halo at around 2 theta = similar to 19 degrees suggesting that polymers were amorphous in nature. In the small-angle region, diffuse to sharp reflections of a typically layered structure resulting from the packing of pentadecyl side chains were observed. The temperature at 10% weight loss (T(10)), determined by TGA in nitrogen atmosphere, of poly(amideimide)s was in the range of 388-410 degrees C indicating their good thermal stability. Glass transition temperatures of poly(amideimide)s were in the range 162-198 degrees C. It was observed that the plasticization effect of attached pentadecyl side chains induced the depression of T(g). (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Cardanol; Cashew nut shell liquid; Pentadecyl chains; Plasticization; Poly(amideimide)s; thermal stability

Synthesis and characterization of aromatic polyazomethines bearing pendant pentadecyl chains - More, Arvind S.; Sane, Prakash S.; Patil, Anandrao S.; Wadgaonkar, Prakash P. (Polymer Degradation and Stability, 2010)
Aromatic diamine monomer viz., 4-(4'-aminophenoxy)-2-pentadecylbenzenamine containing pendant pentadecyl chain was synthesized starting from cashew nut shell liquid - a renewable resource material and was characterized by FTIR, (1)H and (13)C NMR spectroscopy. A series of new (co) polyazomethines containing pendant pentadecyl chains and flexibilizing ether linkages was synthesized by polycondensation of 4-(4'-aminophenoxy)-2-pentadecyl benzenamine with commercially available aromatic dialdehydes viz., terephthaldehyde (TPA), isophthaldehyde (IPA) and varying mixture of TPA and IPA. Inherent viscosities and number average molecular weights of (co) polyazomethines were in the range 0.50-0.70 dL/g and 10,490-40-800 (GPC, polystyrene standard), respectively indicating formation of medium to reasonably high molecular weight polymers. (Co) polyazomethines containing pendant pentadecyl chains were found to be soluble in common organic solvents such as chloroform, dichloromethane, tetrahydrofuran, pyridine, m-cresol and could be cast into transparent and stretchable films from their solution in chloroform. (Co) polyazomethines were essentially amorphous in nature and the formation of loosely-developed layered structure was observed arising from the packing of pendant pentadecyl chains. Polyazomethines exhibited glass transition temperatures (T(g)) in the range 21-48 degrees C. The observed depression of glass transition temperature could be ascribed to the ``internal plasticization'' effect of pentadecyl chains. The temperature at 10% wt loss (T(10)), determined from TGA in nitrogen atmosphere of polyazomethines were in the range 434-441 degrees C indicating their good thermal stability. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Cashew nut shell liquid; CNSL; pentadecyl; polyazomethines; renewable; Side-chain; solubility